2023
DOI: 10.1021/acssuschemeng.2c07759
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Laser Drilling of 3D Porous Current Collectors for High-Capacity Electrodes of Rechargeable Batteries

Abstract: High-capacity rechargeable batteries are crucial for portable electronics, electric vehicles, and smart power grids. Highquality porous Al current collectors with well-designed hole size and hole density are expected to strengthen lithium transportation as well as to accommodate volume variations during fast charging and discharging. Ultrafast femtosecond laser drilling is exploited in this paper to fabricate 3D porous current collectors with precisely controlled hole size and porosity. With optimized laser pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…With the development of electric vehicles and portable electronic devices, there is a growing demand for lithium-ion batteries (LIBs), especially for those with high specific energy, fast charging capability, and high safety. Although the current collector, as an electrochemically inactive component, does not contribute to the energy of the battery, it is an indispensable component and has an important impact on the overall electrochemical performance and reliability of LIBs. , Nowadays, the commonly used current collectors of LIBs are aluminum (Al) foil and copper (Cu) foil due to their nearly irreplaceable economic applicability. However, for the consideration of mobile portability, the obvious drawback of these metallic materials is huge weight, accounting for about 15 and 50% of the total mass of cathode and anode, respectively, , resulting in a huge loss of specific energy of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of electric vehicles and portable electronic devices, there is a growing demand for lithium-ion batteries (LIBs), especially for those with high specific energy, fast charging capability, and high safety. Although the current collector, as an electrochemically inactive component, does not contribute to the energy of the battery, it is an indispensable component and has an important impact on the overall electrochemical performance and reliability of LIBs. , Nowadays, the commonly used current collectors of LIBs are aluminum (Al) foil and copper (Cu) foil due to their nearly irreplaceable economic applicability. However, for the consideration of mobile portability, the obvious drawback of these metallic materials is huge weight, accounting for about 15 and 50% of the total mass of cathode and anode, respectively, , resulting in a huge loss of specific energy of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the rich pore structure of MC−MA fills part of active material so that it has a larger specific capacity, which is similar to other research reports. 10,14,15,24 From the dQ/dV curve in Figure 6b, it can be seen that MC−MA and CC−CA are basically the same during the charge and discharge process, but the reduction peak of CC−CA tends to move to a low voltage direction during the discharge process, and the distance between oxidation peak and reduction peak increases, indicating that CC−CA is more polarized during charge and discharge process. 25 In addition, compared with MC−MA, the reduction peak intensity of CC− CA is weakened, indicating that the capacity released by CC− CA is smaller than that of MC−MA, 26 which is consistent with the results of the charge−discharge curve.…”
Section: Storage Stabilitymentioning
confidence: 99%
“…In recent years, many studies have reported that 3D current collectors have significant advantages in the fast charge and discharge of LIFBs. As a carrier, the current collector not only carries the positive and negative active materials but also completes the current transmission function. It is a key hub for the conversion of chemical energy and electrical energy of LIFBs.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [53] prepared a 3D Al current collector with many micro-sized pores reduced the mechanical stress of the Li metal electrode to prevent internal short circuits. Chen J. Y., et al, [54] proposed an adynamic intelligent Cu current collector with a tuneable pore structure that quickly accommodates volume change caused by the fast plating/stripping of Li under high current densities via modulating the interparticle distances.…”
Section: Transition Metal Materialsmentioning
confidence: 99%